2022
DOI: 10.3390/pharmaceutics14030676
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Tuning of IR-786 for Improved Tumor Imaging and Photothermal Therapy

Abstract: A tumor-targeted near-infrared (NIR) fluorophore CA800Cl was developed based on commercially available IR-786 by modulating its physicochemical properties. IR-786, a hydrophobic cationic heptamethine cyanine fluorophore, was previously recognized as a mitochondria-targeting NIR agent with excellent optical properties. Owing to the poor tumor specificity of IR-786 itself, in vivo studies on tumor-targeted imaging have not yet been investigated. A chloro-cyclohexene ring and indolium side groups on the heptameth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…In the third cycle, the temperature of the HAP800-PEG solutions mostly returned to the ambient temperature after the continuous laser irradiation. This result revealed that the polymethine cyanine backbone of P800SO3 can be damaged by the concentrated NIR light, which is consistent with previous reports [ 33 , 34 ]. After confirming the optimal accumulation time of the tumor site, we performed the in vivo PTT treatment at 24 h post-injection of HAP800-PEG.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In the third cycle, the temperature of the HAP800-PEG solutions mostly returned to the ambient temperature after the continuous laser irradiation. This result revealed that the polymethine cyanine backbone of P800SO3 can be damaged by the concentrated NIR light, which is consistent with previous reports [ 33 , 34 ]. After confirming the optimal accumulation time of the tumor site, we performed the in vivo PTT treatment at 24 h post-injection of HAP800-PEG.…”
Section: Resultssupporting
confidence: 93%
“…According to the previous method [ 35 ], the photothermal conversion efficiency ( η ) of HAP800-PEG was calculated as 34.7%. The η value of HAP800-PEG is similar to that of the polymethine cyanine fluorophores reported previously [ 33 , 34 ]. This result demonstrates that HAP800-PEG can be employed as a promising PTT agent for effective photothermal cancer therapy.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…With increasing the concentration from 100 to 300 µM, the temperature changes of the solution reached approximately from 40 to 80 • C upon 808 nm laser irradiation (1.0 W/cm 2 ) in 2 min. As shown in Figure 3d, the photothermal conversion efficiency (η) of IR-783 was calculated to be 28.9%, which is comparable to that of the heptamethine cyanine dyes reported previously [28,29]. This result suggests that the commercial IR-783 can be applied for in vivo photothermal tumor ablation.…”
Section: In Vitro Cytotoxicity Cell Binding and Photothermal Effectsupporting
confidence: 79%
“…24 As different chemical couplings can alter the structure of the targeted ligand, the fluorescence imaging ability, and the therapeutic potential. 25 We successfully synthesized IR-817, a new near-infrared fluorescent dye, by coupling IR-808 with dicyclohexylcarbodiimide in our previous study. 26 The in vitro and in vivo imaging studies revealed that IR-817 functioned as an excellent melanoma-targeting agent.…”
Section: Introductionmentioning
confidence: 99%